2020
DOI: 10.1177/0961203320937783
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Colombian patients with systemic lupus erythematosus and its correlation with disease activity

Abstract: Introduction Patients with systemic lupus erythematosus (SLE) frequently present low levels of vitamin D. However, studies that have evaluated its association with disease activity have generated contradictory results. Methods A cross-sectional study was carried out on patients diagnosed with SLE in two hospitals in Manizales, Colombia. Disease activity was evaluated by the SLE disease activity index 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Serum levels of 25(OH) Vit D have been measured as 25(OH) Vit D is the most abundant circulating metabolite of Vit D, with a half-life of 2–4 weeks, making it the best predictor of Vit D deposits and supplementation response. 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of 25(OH) Vit D have been measured as 25(OH) Vit D is the most abundant circulating metabolite of Vit D, with a half-life of 2–4 weeks, making it the best predictor of Vit D deposits and supplementation response. 9…”
Section: Methodsmentioning
confidence: 99%
“…All patients fulfilled the classification criteria for SLE by Systemic Lupus Collaborating Clinics (SLICC) 2012. 7 Data collection and assessment 9 The plasma vitamin D concentrations were assessed for all subjects studied using EDI TM Total 25-OH Vit D EIA kit (Epitope Diagnostics, Inc., San Diego, USA). In contrast, plasma IFN-c and IL-17 concentrations were determined by using Human IFN-c and IL-17 ELISA (enzyme-linked immunosorbent assay) kit (Elabscience, Elabscience Biotechnology Co., Ltd) Under the protocol of the supplier.…”
Section: Study Subjectsmentioning
confidence: 99%
“…A quantitative decrease of 25(OH)D in serum can decrease CYP27B1 activity in immune cells, reduce the local concentration of 1,25(OH) 2 D 3 , and attenuate the corresponding immune regulatory mechanism. Dutta C [ 13 ] and other researchers [ 14 ] have demonstrated that SLE patients with vitamin D deficiency are more likely to have high disease activity, and patients with a high SLEDAI score (>10) also have a greater risk of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…56 The same conclusion was made by other researchers. [57][58][59] In contrast, Ruiz-Irastorza et al, as well as Miskovic et al, found no association between vitamin D insufficiency or deficiency and the SLEDAI in patients with SLE. 16 60 In recent years, more and more evidence has emerged regarding the immunoregulatory effects of vitamin D. The effect of vitamin D on the specific immune response occurs by suppressing T cell proliferation and switching T helper phenotypes, reducing the immune response of type 1 T helpers, inhibiting the production of type 1 proinflammatory cytokines such as IL-12, interferon-γ, IL-6, IL-8, tumour necrosis factor (TNF)-α and IL-9.…”
Section: Lupus Science and Medicinementioning
confidence: 94%